Knowledge, beliefs and behaviours related to STD risk, prevention, and screening among a sample of African American men and women. (May 2014) - Uhrig, Jennifer D; Friedman, Allison; Poehlman, Jon; Scales, Monica; Forsythe, Ann
Objective: Current data on sexually transmitted disease (STD) among African Americans show significant racial/ethnic disparities. The purpose of this study was to explore knowledge, attitudes, beliefs, and behaviours related to STD risk, prevention, and testing among African American adults to help inform the development of a health communication intervention to address the high rates of STDs in this community. Design: Cross-sectional survey. Setting: Four United States (US) communities with high cumulative incidence of STDs. Method: We administered a 44-item structured survey. Results: Participants were 185 sexually active heterosexual African Americans aged 18 to 45. Most participants (84.2%) had been tested for an STD at least once. Most participants (75.8%) perceived STDs to be a problem in their community, and almost all (91.2%) felt that people needed education to learn how to avoid STDs. Nonetheless, only half of participants (49.5%) agreed that they should get tested for STDs because they may be at risk. Misconceptions related to STD prevention and testing were identified. Results suggest that STDs remain highly stigmatized with concerns related to social and interpersonal consequences. Participants' perceived personal risk was low, despite acknowledging high STD rates in their communities. Conclusion: Findings suggest that health communication may play an important role in addressing STD disparities by increasing perceptions of personal risk, minimizing STD-associated stigma, and marketing STD prevention and testing behaviours.